Role of health technology assessment in the process of implementation of the EU Transparency Directive: relevant experience from Central Eastern European countries - Kolasa, Katarzyna; Kalo, Zoltan; Zah, Vladimir; Dolezal, Tomas (Expert review of pharmacoeconomics & outcomes research, 2012)
A total of 7 years after the addition of Poland, the Czech Republic and Hungary to the EU, the pricing and reimbursement regulations introduced in these countries are still considered to be not fully compliant with Directive 89/105/EEC, commonly referred to as the 'Transparency Directive' (TD). The TD aims to ensure the transparency of the pricing and reimbursement processes for medicinal products established by the member states. Among the most difficult barriers on the way to successful implementation of the TD discussed are meeting the timelines indicated by the TD, the implementation of objective and verifiable criteria for decisions, and the availability of remedies for negative decisions. Health technology assessment (HTA) has been introduced in to the reimbursement systems in Poland, the Czech Republic and Hungary almost simultaneously to their accession to the EU. Even though Central Eastern European (CEE) countries faced similar challenges during the transformation to a democratic system, certain differences in the extent to which HTA principles have been implemented in these countries could be distinguished. Hence, it is thought-provoking to consider the different views of HTA experts on the role of HTA in the adaptation of the TD in the CEE region. The key objective of this article will be to discuss whether the adaptation of HTA principles has supported or only triggered additional challenges in the process of successful implementation of the TD in the CEE region. In particular, the article will discuss whether the introduction of mandatory HTA recommendations or explicit willingness-to-pay threshold would encourage or discourage implementation of the TD. The importance of the independent HTA agency as a condition for successful introduction of the TD will also be debated.
Keywords: hodnocení biomedicínských technologií; Hungary; Česká republika; Time Factors; časové faktory; Humans; Reimbursement Mechanisms; lidé; Technology Assessment, Biomedical; Maďarsko; Evropská unie; dávkové mechanismy; Poland; náklady a analýza nákladů; Czech Republic; European Union; Costs and Cost Analysis; Polsko